The Silence We Inherit: A Memoir and Beneath the Carpet: A Critical Reflection on Trauma, Voice, and the Second-Person in Life Writing - Touhey, Joanne (Trinity College Dublin. School of English. Discipline of English, 2026)
This thesis explores the representation of trauma, silence, and voice in contemporary memoir through a dual submission comprising a creative work, The Silence We Inherit, and a critical reflection, Beneath the Carpet. The memoir examines intergenerational trauma, secrecy, and resilience, employing a blend of first- and second-person narration to articulate experiences that are often silenced or fragmented. The accompanying critical essay investigates the function of second-person voice in life writing as a strategy for representing dissociation, disclosure, and ethical self-narration. Drawing on trauma theory and close readings of contemporary memoirs, it considers how narrative form shapes the articulation of difficult or unspeakable experiences. Together, the creative and critical components interrogate the relationship between memory, identity, and narrative voice, challenging conventional boundaries between lived experience and literary form while demonstrating how memoir can act as both personal testimony and cultural intervention.
APPROVED
Keywords: Memoir; Trauma; Memory; Second-person narration; Intergenerational Trauma; Voice; Life writing